Aerosol Jet® printing of optical waveguides - Reitberger, Thomas; Hörber, Johannes; Schramm, René; Sennefelder, Simon; Franke, Jörg (38th International Spring Seminar on Electronics Technology, ISSE 2015, 2015)

Electrical and mechanical investigations on copper circuit paths coated on fiber-reinforced plastics by atmospheric plasma technology - Schramm, René; Reitberger, Thomas; Franke, Jörg (Journal of Microelectronics and Electronic Packaging, 2015)
Keywords: Additive metallization; Atmospheric plasma coating; Characterization; Plastics

Electrical Characterization of Fibre-Reinforced Plastics by Atmospheric Plasma Technology - Schramm, René; Reitberger, Thomas; Franke, Jörg (2014)

Electrical functionalization of thermoplastic materials by cold active atmospheric plasma technology - Schramm, René; Franke, Jörg (Proceedings of the 2013 IEEE 15th Electronics Packaging Technology Conference, EPTC 2013, 2013)
Plasmadust® is a new technology using cold active plasma for additive metallization of different substrate materials. For electronics production, in particular Molded Interconnect Devices (MID), thermoplastic materials can be structured with copper as power electronic conductive pattern. The main advantages of Plasmadust® are the controllable process temperature range between about 90°C and 180°C, the good adhesion of the metallization, the fast process speed of about 100 mm/s and the fast growing conductor tracks with about 15 microns thickness per cycle. Plate specimens were made of PA, a thermoplastic commonly used in automotive applications, with different process parameters. Conductor tracks applied onto the substrates consist of one line with different electrical and mechanical properties according to the process temperature and process speed. Additionally, the thickness and the width of the conductor track depend on the process parameters. The setting of the process speed turns out to be an important influence on the thickness and roughness of the conductor track that can be achieved on thermoplastic substrates. The investigated combination of thermoplastic and copper shows a constant bonding performance during thermal shock testing for 1000 cycles in the range of-40°C and +125 °C. An exposure to humidity heat (85 % r.h / 85°C) for 500 h has only marginal effects on the adhesion of the printed structures on the thermoplastic substrates, too. This highly promising results provide the base for further investigations to achieve a sufficient ampacity related to standard chemical PCB metallization processes. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07

Electrical functionalization of thermoplastics by combining plasmadust coating and aerosol jet printing - Schramm, René; Hörber, Johannes; Dold, Christoph; Franke, Jörg (Advanced Materials Research, 2014)
Additive structuring and metallization technologies like Plasmadust or Aerosol Jet printing offer many advantages for future MID applications. Both digital writing technologies enable a highly flexible design of the circuit pattern and are capable of coating 3D substrates. Currently, Aerosol Jet printing is used to generate patterns with accurate and detailed features, and line widths of 100 μm. Plasmadust provides variable coating thicknesses up to 200 μm combined with a high process speed. Hence, a combination of both technologies appears to be advantageous for a broad range of MID applications. In this paper an initial study on the interconnection of plasmadust and Aerosol Jet generated conductive structures on thermoplastic substrate materials is presented. In this context different printing strategies and process variations are evaluated.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Additive metallization; Aerosol jet; Plasmadust; Structuring

Investigations in the optimization of power electronics packaging through additive plasma technology - Franke, Jörg; Syed Khaja, Aarief Hussain; Schramm, René; Ochs, Raimund (4th CIRP Global Web Conference, CIRPe 2015, 2015)
Due to thermomechanical stresses at high temperatures and harsh environments, the interconnections between the substrate and the components in power electronics exhibit failure modes at temperatures >130°C. This contribution introduces the concept of additive plasma metallization technology for the optimization of interconnections in electronics for reliable usage up temperatures >300°C. Through the formation of intermetallic phases, diffusion soldered interconnections were realized by melting of solder paste with plasma based copper powder coating. The integration of the Plasmadust technology into standard production process delivers highly reliable interconnections with better resource management. The interconnections were characterized by building power electronic modules to demonstrate the advantages compared to state-of-the-art technologies. The potential of the Plasmadust process for power electronic production and further chances in component modification are discussed.
Keywords: Additive manufacturing; High temperature capability; Intermetallics; Plasmadust; Power electronics

Manufacturing of 3D mechatronic systems with plasma technology - Schramm, René; Franke, Jörg (Smart Systems Integration - 8th International Conference and Exhibition on Integration Issues of Miniaturized Systems - MEMS, NEMS, ICs and Electronic Components, SSI 2014, 2014)
CRIS-Team Scopus Importer:2023-03-07